1986
DOI: 10.1111/j.1365-2141.1986.tb07582.x
|View full text |Cite
|
Sign up to set email alerts
|

Different platelet specificities of heparin‐dependent platelet aggregating factors in heparin‐associated immune thrombocytopenia

Abstract: Delayed onset heparin-associated thrombocytopenia (HAT) is thought to be a result of formation of antiplatelet antibodies which cause platelet aggregation in the presence of heparin. Platelet aggregation in response to serum from patients with HAT has been studied in platelet-rich plasma (PRP) from a panel of normal blood donors. Heparin-dependent aggregation with any HAT serum occurred in PRP from only some donors. PRP from the non-responding donors did, however, aggregate in the presence of heparin with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…1 Despite having thrombocytopenia, affected patients usually develop thrombosis, and this particular clinical presentation is explained by the central role of Fcg receptors in the pathophysiology of HIT, particularly FcgRIIA, which mediates platelet activation induced by immunoglobulin (Ig) G-PF4/H immune complexes (ICs). In addition, platelets from healthy donors exhibit wide variability in their response to HIT antibodies, [2][3][4] and many patients who synthesize significant levels of antibodies to PF4/H while being treated with heparin do not develop HIT. [5][6][7] The FCGR2A gene, which encodes FcgRIIA, displays a functional allelic dimorphism generating 2 codominantly expressed allotypes with either a histidine (H) or an arginine (R) at amino acid position 131 in the second Ig-like extracellular domain.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite having thrombocytopenia, affected patients usually develop thrombosis, and this particular clinical presentation is explained by the central role of Fcg receptors in the pathophysiology of HIT, particularly FcgRIIA, which mediates platelet activation induced by immunoglobulin (Ig) G-PF4/H immune complexes (ICs). In addition, platelets from healthy donors exhibit wide variability in their response to HIT antibodies, [2][3][4] and many patients who synthesize significant levels of antibodies to PF4/H while being treated with heparin do not develop HIT. [5][6][7] The FCGR2A gene, which encodes FcgRIIA, displays a functional allelic dimorphism generating 2 codominantly expressed allotypes with either a histidine (H) or an arginine (R) at amino acid position 131 in the second Ig-like extracellular domain.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Other functional methods have therefore been developed, such as the heparin-induced platelet activation test, performed in microplates with washed platelets,An enzyme-linked immunosorbent assay (ELISA; Asserachrom-HPIA; Diagnostica Stago, Asnieres, France) has been developed that detects antibodies that bind to H-PF4 complexes covalently coated in microwells at optimal concentrations. 1213 This ELISA technique apparently provides higher sensitivity than platelet aggregation or activation tests 1415 and can detect antibodies to H-PF4 in patients receiving heparin before thrombocytopenia develops.…”
Section: The Value Of the Platelet Aggregation Test Carbon 14-labelementioning
confidence: 99%
“…Several groups have demonstrated that the IgG fraction of HAT sera activates platelets in the presence of heparin [7][8][9][10]. In spite of parenteral anticoagulation and throm bocytopenia, these patients are at risk of developing se vere arterial and venous thromboembolic complications, resulting in a high rate of morbidity and mortality [11].…”
Section: Introductionmentioning
confidence: 99%